2008
DOI: 10.1180/claymin.2008.043.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Clay minerals in the Namacotche Pegmatite Group from Zambezia Province, Mozambique: main constituents of late-stage secondary paragenesis

Abstract: AB ST R ACT : Namacotche gem-bearing pegmatites of Alto Ligonha pegmatite district are heterogeneous, strongly fractionated, and have large Li and Ta and extremely large Cs contents. Clay samples were collected in fracture infillings and dilation cavities with gemstones and were studied using X-ray diffraction (XRD), polarized light microscope, scanning electron microscopy-energy dispersive spectroscopy, high-resolution transmission electron microscopy and chemical analyses. The <2 mm fraction contains cookeit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Numerous previous investigators of inclusions have reported the presence of moderate-to low-salinity aqueous carbonic fluid inclusions in both normal and highly evolved pegmatites (e.g., Channer et al 1999, Fuertes-Fuente et al 2000, Beurlen et al 2001, Sirbescu & Nabelek 2003, Thomas et al 2010. Such aqueous carbonic fluids are known to have reacted with lithium aluminosilicates to produce a low temperature (250-300°C) cookeite-bearing assemblage of alteration minerals (Černý 1972, Sequeira Braga et al 2008. In their study of the alteration of spodumene in aplite-pegmatite suites from northern Portugal, Bobos et al (2007) showed that surface dislocations, cleavages, and fractures in spodumene are sites of excess energy, where the mineral dissolves more readily.…”
Section: Polyphase Inclusions In Spodumenementioning
confidence: 97%
“…Numerous previous investigators of inclusions have reported the presence of moderate-to low-salinity aqueous carbonic fluid inclusions in both normal and highly evolved pegmatites (e.g., Channer et al 1999, Fuertes-Fuente et al 2000, Beurlen et al 2001, Sirbescu & Nabelek 2003, Thomas et al 2010. Such aqueous carbonic fluids are known to have reacted with lithium aluminosilicates to produce a low temperature (250-300°C) cookeite-bearing assemblage of alteration minerals (Černý 1972, Sequeira Braga et al 2008. In their study of the alteration of spodumene in aplite-pegmatite suites from northern Portugal, Bobos et al (2007) showed that surface dislocations, cleavages, and fractures in spodumene are sites of excess energy, where the mineral dissolves more readily.…”
Section: Polyphase Inclusions In Spodumenementioning
confidence: 97%